Information technology, transaction costs and governance structures: integrating an institutional approach - Islamoglu, Mehmet; Liebenau, Jonathan (Sage Publications Ltd, 2007)
Transaction cost concepts have been deployed in information systems to analyze the impact of information technology on the organization of economic activity in markets and hierarchies. It has been widely observed that there is a general trend toward markets. It has also been observed that the transaction cost approach cannot explain empirical observations where the choice of governance has more to do with power and behavioral attributes of transacting actors than with minimizing transaction costs. Information systems researchers have overcome the shortcomings of the transaction cost approach to a limited extent by complementing it with political economy, resource- dependency and network theories. However, these complementary perspectives cannot easily analyze the interactions between power and efficiency and cannot handle the impact of the institutional environment on the choice of governance structure. This research exposes the shortcomings of these complementary perspectives in the light of a range of institutionalist studies drawn from economics, sociology and anthropology. The research points out that an institutional approach is essential for understanding and overcoming the complications that may arise as IT- enabled moves toward markets are launched in organizations that are situated in institutional environments that are at present not compatible with market- oriented exchange arrangements. We demonstrate this by the application of three 'tools' to an exemplary case where information systems in the British National Health Service were intended as a tool to move one aspect of the hierarchical structure toward a market structure.
Keywords: transaction costs; governance; electronic markets; institutional economics; health information systems